(untitled) (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2023)
Abstract Increasingly complex and interdependent issues in the public sector make the need for cooperation and collaboration even more urgent. Innovation through collaboration is the essence of the concept of open innovation which must seek interaction with external agents to create ideas and improve services. This work consists of 25 systematic literature review articles to synthesize and critically review collaborative governance in the public sector. The detailed objectives are as follows: to summarize the evidence on the phenomena and characteristics of collaborative governance; analyze the supporting variables of collaborative governance; and analyze the field of application of collaborative governance in the public sector. The authors’ findings show that: First, in recent years there has been an increasing interest in collaborating on public policy; Responding to the interconnected and complex nature of the issues currently facing governments, academics and practitioners alike have focused on governance processes that blur the boundaries between the public, private, and community sectors; Second, there are many characteristics of collaborative governance as collaborative innovations that have not been used as research variables; Most of the variables used are more dominant to external organizational factors. Third, collaborative governance alludes a lot to technology and there are still many areas of public service that have not been studied in its application; as many as 19 areas of application of collaborative governance have been analyzed in this work.